Jakościowa perspektywa na badania ilościowe. Problematyczność konstrukcji narzędzi kwestionariuszowych na przykładzie kwestionariusza KADS = Qualitative perspective on quantitative research. A critical analysis of kutcher adolescent depression scale - Opaliński, Konrad (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Psychological questionnaires are most common scientific tools in the field of psychology, in accordance to quantitative methodology of social sciences. Main critique of this science paradigm base on difficulty in objectification of subjective mental states and the discount of contexts not related to the scientific study.
Keywords: badania jakościowe; kwestionariusz KADS; discursive psychology; qualitative methods; KADS Scale